The rise of Ethiopian churches in Nigeria: a reaction against religious colonisation in Africa (2022)
Colonisation of Africa by the European nations in the 19th century could be adjudged as a means of development in some facets of life, yet its resultant effects among others was cultural enslavement of the indigenes. Such negative effect was rebuffed by a few educated A fricans withnationalistic consciousness. In a similar vein, A frican Christians reacted against what can be termed religious colonisation orchestrated by European Missionaries who among other evils, ostracised African Christians from the mainline churches because of polygamy, condemned the institution of chieftaincy and grossly discriminated against the natives in the polity of the Church. The inhuman treatment of Bishop Samuel Ajayi Crowther and Rev James Johnson exemplified this anti-African attitude of the European Missionaries. Hence the emergence of Ethiopian Churches in Nigeriatowards the end of the 19th century and at the turn of the 20th century served as a religious expression of nationalism in Africa. There fore, this paper seeks to investigate the dynamism of religious expressions of nationalism in Nigeria as typified by The African Church and others with nationalistic tendencies with a view to determining how the claims of religious nationalists interfaced with Henry Venn's principles of evangelisation in Africa. Historical method was adopted for the collection of data.